Enhanced Wearable Strap for Feminine using IoT - Kumar, Sathish; Nandhini, S; Sujitha, R (Universitas Komputer Indonesia, 2022)
Women are increasingly experiencing a slew of security difficulties while traveling alone at night, particularly in the IT industry. Despite the benefits of new technologies, the rate of crime against women continues to rise. Despite the fact that numerous security gadgets are available on the market, women are unaware of them and do not use them. We are going to develop a prototype design using IoT. The term